MENURUNNYA PENUTUR BAHASA INDONESIA SEBAGAI LINGUA FRANCA - Tato Nuryanto (Jurusan Tadris Bahasa Indonesia, 2015)
Indonesian has a position and a very important function, as listed in the 1928 Youth Pledge pledge which reads Our sons and daughters of Indonesia to uphold the national language, Indonesian. In plain view, the younger generation and the public are still many who do not know about the position and function of Indonesian. There it is forgotten that the Indonesian actually has a function as a symbol of the pride of nationhood, national identity, means of transportation atarwarga, interregional and intercultural, as well as tools that allow the unification of the various ethnic groups with socio-cultural background and language of each into a unitary national Indonesia , It is very clear that the Indonesian association as an intermediate language (lingua franca) from time immemorial.